Perception of motorcyclists on safe riding in Kota Kinabalu - M. I., Saibin; Haryati, Yaacob; S. A., Hassan; A. Ismail, Mohamed; S. N. N., Kamarudin; Putra Jaya, Ramadhansyah; Al-Safar, Z. H.; E., Shaffie (IOP Science, 2023)
Despite the high risks reflected from the annual road traffic casualties, motorcycles remain a popular mode of transport in Malaysia due to economic and ease-of-use factors. Therefore, various parties need to play their roles, make proper plans and take actions to accommodate the needs of the motorcyclists in Malaysia. Consequently, some fundamental basis on how motorcyclists interact with the road environment and other drivers was needed. For this reason, this study was to examine and assess motorcyclist perception towards safe riding regarding the road environments and other drivers' attitude and behaviour. A survey by distributing questionnaires among motorcyclists in Kota Kinabalu, Sabah was conducted and was analysed using Statistical Package for Social Science (SPSS) tools. It found that most motorcyclists, regardless of their demographic and riding background, perceive that poor road conditions such as road surface defects and slippery roads highly affect their safe motorcycling. Besides that, there was no statistically significant difference between motorcyclists' perceptions of positive and negative attitudes and behaviour. These findings also guide the development of any road safety initiatives and strategies, as well as for future studies specifically related to motorcycle concerns.